The method of maintenance efficiency estimation of the food supply service’s objects of the military unit of the Interior Troops of the Ministry of Internal Affairs of Ukraine - Vasilenko, V. P.; Bondarenko, O. H.; Kaplun, S. O. (Honor and Law, 2019)
A methodological approach to military-economic assessment of the activity of the logistic supply services’ objects of the military unit is revealed, on food supply service example. A proposal of the use of an integrated criterion of military-economic assessment of the food supple service activities, which is calculated as the ratio of the integrated indicator of the economic effect to the cost of the annual maintenance service is justified. A methodic for the necessary calculation and the procedure of making decisions on their basis are proposed.